Exploring Circular Digital Economy Strategies for Sustainable Environmental, Economic, and Educational Technology - Wilson, Ashley; Kask, Rasmus; Ming, Li Wei (International Transactions on Education Technology (ITEE), 2024)
This research explores the strategic implementation of digital economy principles to achieve environmental sustainability and economic prosperity, utilizing the SmartPLS method. In an era marked by heightened awareness of environmental challenges and the urgent need for sustainable economic solutions, the digital economy emerges as a promising and innovative approach. This study primarily focuses on the integration of digital technologies throughout the product and service life cycle, with the objectives of extending product longevity, minimizing waste, and enhancing resource efficiency. Through an extensive review of literature and multiple case studies, we delve into various dimensions of the digital circular economy. These dimensions include innovative business models, the pivotal role of consumers, the challenges encountered during implementation, and their overall impact on economic growth. The findings underscore the crucial importance of cross-sectoral collaboration and the formulation of supportive policies to unlock the full potential of this economic model. Moreover, this research highlights the synergies between digital transformation and circular economy practices, suggesting that their convergence can significantly drive sustainable progress in contemporary society. By presenting comprehensive insights into the digital economic cycle, this study aims to contribute to the discourse on sustainable innovation and provide a roadmap for policymakers, businesses, and researchers to foster a more sustainable and prosperous future.